DIGITALISASI NARASI BUDAYA LOKAL SEBAGAI STRATEGI PENGUATAN KOMUNIKASI DAN BRANDING PARIWISATA BERKELANJUTAN BERBASIS KOMUNITAS DI SIOMPU KABUPATEN BUTON SELATAN - Fida, Wa Nur; Mayunita, Sry; Al-Ghaniyuh, L.M. Zoqroh; Tan, Chelsea (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Culture-based tourism is a strategic sector of sustainable development, but its potential has not been maximized due to weak digital communication capacity and suboptimal cultural narratives. This service activity aims to empower local communities through digitizing cultural narratives to strengthen destination identity and tourism competitiveness. The methods include cultural potential mapping, digital storytelling training, digital content production (video, podcast, social media), and digital branding implementation. As a result, the digitization of cultural narratives increases community media literacy and active participation in building an authentic destination image. The program also strengthened intercultural communication and tourism promotion networks, produced digital content, social media platforms, and replicable training modules. This approach has proven effective as an innovative strategy for community-based sustainable tourism development.